Nasal bone fracture timely interventon is a need - Manjunath, KN (Bangladesh Journal of Otorhinolaryngology, 2013)
Nose is acentral projection in the face with fragile skeleton. A trivial trauma canose is acentral projection in the face with fragile skeleton. A trivial trauma can result in a significant deformity. Although majority suffer a bony injury, overlying swelling masks the deformity. If such deformity is not identified and intervened, it can lead to soft tissue changes as well as bone deformity, which may require septoplasty or rhinoplasty later hence in nasal bone fracture intervention in the timely manner is a must to reduce the long term morbidity and the cost of treatment result in a significant deformity. Although majority suffer a bony injury, overlying swelling masks the deformity. If such deformity is not identified and intervened, it can lead to soft tissue changes as well as bone deformity, which may require septoplasty or rhinoplasty later hence in nasal bone fracture intervention in the timely manner is a must to reduce the long term morbidity and the cost of treatment. DOI: http://dx.doi.org/10.3329/bjo.v19i1.12066 Bangladesh J Otorhinolaryngol 2013; 19(1): 11-13